Efficient one pot and chemoselective synthesis of functionalized 3-bromo-4, 5-dihydroisoxazole derivatives via 1, 3-dipolar cycloaddition reactions of nitrile oxides. Issue 48 (30th November 2017) - Alizadeh, Abdolali; Roosta, Atefeh; Rezaiyehrad, Reza; Halvagar, Mohammadreza
Abstract: A novel, metal-free and chemoselective approach for the synthesis of 4, 5-dihydroisoxazole derivatives has been developed by the reaction of readily accessible starting materials including 4-oxo-4 H -chromene-3-carbaldehyde, 1-phenyl-2-(1, 1, 1-triphenyl- λ 5 -phosphanylidene)ethan-1-one and dibromoformaldoxime under mild conditions in the presence of KHCO3 . Graphical abstract: